2001
DOI: 10.1590/s0103-90162001000400017
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of soybean via embryogenic suspension culture

Abstract: In an attempt to establish an alternative plant regeneration system for soybean [Glycine max (L.) Merrill] cultivars used in Brazilian breeding programs, ten genotypes were tested for their embryogenic potential. Cotyledons were removed as explants from immature seeds harvested from field-grown plants. After 45 days on induction medium, the number of responding cotyledons and the number of somatic embryos per immature cotyledon were evaluated. The percentage of explants that produced somatic embryos varied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
4
18
1
Order By: Relevance
“…That study only assessed somatic embryo induction stage. Other studies also reported the high capacity of IAS-5 to produce somatic embryos (Santos et al, 1997;Di Mauro et al, 2000;Droste et al, 2001). More recently, Droste et al (2010) identified Brazilian soybean genotypes with potential to respond to in vitro culture stimuli for somatic embryo induction, embryo proliferation and plant regeneration.…”
Section: Genotype-dependent Response and Screening Of Highly Responsimentioning
confidence: 89%
See 4 more Smart Citations
“…That study only assessed somatic embryo induction stage. Other studies also reported the high capacity of IAS-5 to produce somatic embryos (Santos et al, 1997;Di Mauro et al, 2000;Droste et al, 2001). More recently, Droste et al (2010) identified Brazilian soybean genotypes with potential to respond to in vitro culture stimuli for somatic embryo induction, embryo proliferation and plant regeneration.…”
Section: Genotype-dependent Response and Screening Of Highly Responsimentioning
confidence: 89%
“…Subsequently, several papers have reported the development of somatic embryos from cotyledons of immature embryos. But until today the measured frequencies at which these embryos convert into plants are significantly lower than that expected (Parrott et al, 1988;Meurer et al, 2001;Droste et al, 2001Droste et al, , 2010. Therefore, efforts have been directed towards developing and refining protocols for initiation, proliferation, and histodifferentiation/maturation of soybean somatic embryogenesis.…”
Section: Optimization Of Soybean Somatic Embryogenesis Protocolmentioning
confidence: 98%
See 3 more Smart Citations